2011
DOI: 10.1089/cyber.2010.0492
|View full text |Cite
|
Sign up to set email alerts
|

The Pervasiveness, Connectedness, and Intrusiveness of Social Network Site Use Among Young Adolescents

Abstract: Young adolescents are quickly becoming avid users of social networking sites (SNSs); however, little is known regarding how they use these sites. The goal of the present study was to examine the extent to which young adolescents use SNSs, with whom they connect via these sites, and whether SNS use disrupts daily functioning. Among 268 middle-school students surveyed, 63% reported having their own profile page on an SNS. On average, adolescents reported having 196 SNS contacts (friends), most of whom were known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 16 publications
4
68
1
2
Order By: Relevance
“…Regarding the possible association between social media and poor sleep quality, Espinoza (2011) found that 37% lost sleep due to using social networking applications. Woods and Scott16 stated that, using social media involves continued alerts at all times of the day.…”
Section: Figure (1) Medical Students' Quality Of Sleep Discussionmentioning
confidence: 99%
“…Regarding the possible association between social media and poor sleep quality, Espinoza (2011) found that 37% lost sleep due to using social networking applications. Woods and Scott16 stated that, using social media involves continued alerts at all times of the day.…”
Section: Figure (1) Medical Students' Quality Of Sleep Discussionmentioning
confidence: 99%
“…Research have shown that internet addiction, social media addiction, smartphone addiction and digital game addiction are associated with "depression" (24)(25)(26)(27), "impulsivity" (7,(28)(29)(30), "loneliness" (31)(32)(33)(34), "sleep quality" (25,27,35,36), "well-being" (25,(37)(38)(39), "self-esteem" (33,34,40,41) and "academic performance" (24,(42)(43)(44). On the other hand, according to some researchers, the use of technology strengthens friendship, facilitates interpersonal conversations and communication, and allows establishing new social relations (45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…And also it cause some other problems like; low selfesteem, high levels of timidness and loneliness (Julia et al 2014), heart rate increase (Griffiths and Dancaster, 1995), well-being (Demirci et al 2015), sleep quality (Espinoza & Juvonen 2011), aggressiveness and impulsivity (Wo, 2003), academic performance (Brunborg et al 2014;Skoric et al 2009), social life and emotional functioning (Turel et al 2011) psychological issues; depression, compulsion, suicidal tendencies, attention shortfall as well as hyperactivity (Julia et al 2014) and low self-admission (Montag et al 2011) positively associated with problematic gaming propensities. According to Wood et al (2007), the common outcome is time lost, and spending too much time on one activity can compose its problems.…”
Section: Introductionmentioning
confidence: 99%